TIPE PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH MENENGAH ATAS (SMA) - Nuryani Nuryani; Hera Febriana (Department of Indonesia Language and Literature Teaching, UIN Syarif Hidayatullah Jakarta, 2017)
Abstract: This study aimed to describe the type of Indonesian language learning implemented in SMA Negeri 1 Ciawi, Social Class X. Qualitative method is employed in this research in order to describe the research object. The technique used to collect data was questionnaire, observation or direct observation in the classroom, and conduct interviews. The results showed that the type of Indonesian language learning that took place at SMA Negeri 1 Ciawi, Social Class X is integrative type. Integrative type is a type of language learning in which students do not just learn the language, but everything they learned in school are applied in everyday life. Through the questionnaire knows as much 67% students show a positive attitude towards Indonesian language. In addition, strengthened by the result of observations show seven teachers' activities also led to a positive attitude towards Indonesian. Abstrak: Penelitian ini bertujuan mendeskripsikan tipe pembelajaran Bahasa Indonesia di kelas X IPS SMA Negeri 1 Ciawi. Metode deskriptif kualitatif digunakan dalam penelitian ini bertujuan untuk memaparkan objek penelitian tanpa memanipulasi data. Teknik pengumpulan data yang digunakan adalah penyebaran angket, pengamatan atau observasi di kelas, dan melakukan wawancara. Hasil penelitian menunjukkan bahwa tipe pembelajaran Bahasa Indonesia di kelas X IPS SMA Negeri 1 Ciawi yaitu tipe integratif. Tipe integratif mengarah pada pembelajaran bahasa yang membentuk sikap positif bahasa. Melalui angket diketahui bahwa 67% siswa menunjukkan sikap positif terhadap bahasa Indonesia. Demikian juga dengan angket guru, yakni sebanyak tujuh guru melakukan proses pembelajaran bahasa yang mengaraj pada tipe integratif. Permalink/DOI: http://dx.doi.org/10.15408/dialektika.v4i1.7000